Hubungan Lingkar Kepala Dengan Prestasi Belajar Pada Anak SD N 1 Tambongwetan Kalikotes - anna Uswatun (Universitas Muhammadiyah Klaten, 2019)
Brain growth is one of the things that changes, if nutritional intake is reduced, some parts of the brain development will be disrupted. The result of malnutrition will result in obstruction of the body and brain development, where head circumference is used as a parameter to determine it. In the growth parameters, there are several body parts that are measured including body weight, height, head circumference and chest circumference, if there is one that is less than normal it can affect learning achievement. The purpose of this study was to find out